PELATIHAN REMOTE LABORATORY PADA PEMBELAJARAN PRAKTIK PLC DI SMK - Neris Peri Ardiansyah; Ajeng Mayang Kurniaviep Sugeng; Ase Sunarya; Yudi Barnadi (Jurnal Ilmiah Teknologi Infomasi Terapan, 2022)
The use of Remote Laboratory in Practical Learning which is carried out in Vocational High Schools when online learning is carried out, is widely used to fulfill practical learning achievements. Training is carried out for vocational school teachers who have competence in the field of practice, as well as development in learning media. During the implementation of the activity, the ability to manage and use the Remote Laboratory is given to be adapted to the right learning model in learning PLC practical lessons. From the results of the training carried out, the results obtained where activity participants can apply the use of remote laboratories with results that can be applied directly to vocational students. From the results of the training, it is obtained that the level of mastery of the participants in terms of operating the Remote Laboratory can be mastered in accordance with the minimum criteria for assessment. Remote Laboratory can directly provide direct learning experiences such as carrying out practical learning in the laboratory.